Evaluasi Kualitas Data Pada Daftar Produk Tayang Di Katalog Elektronik Versi 6.0 - Pratiwi, Aprilia; Mahsa Elvina Rahmawyanet; Amanda Ghaisani; Tri Broto Siswoyo; Yova Ruldeviyani; Yudho Giri Sucahyo (AI Society & STMIK Indonesia, 2025)
Data quality is important aspect in supporting transparency, accountability, and efficiency of the government procurement process. Electronic Catalog data acts as a source of information on products, services, and providers of goods/services. The transition from Electronic Catalog v5 to v6 is form of digital transformation in the government procurement of goods/services as form of improving public services. Measuring the quality of Electronic Catalog v6 data has significant role in providing effective, efficient and accountable information. This study aims to evaluate the quality of data on Electronic Catalog v6 product data using the Total Data Quality Management (TDQM) framework. There are 6 dimensions used in evaluating data quality, completeness, accuracy, data integrity, fairness, consistency, and precision. The results of the study show that the dimensions of consistency, accuracy, completeness, fairness and precision reach above 90% while data integrity reaches below 50% and requires improvement on product data quality.